Substitution of Inorganic Fertilizer and Biofertilizer Application on Wetland Rice (Oryza sativa) Varieties Inpari 32 - Rimbasari, Marvita Akhiri; Tyasmoro, Setyono Yudo; Wicaksono, Karuniawan Puji; Hariyono, Didik (International Journal of Environment, Agriculture and Biotechnology, 2024)
This research aims to determine the substitution of inorganic fertilizers using organic fertilizers and biofertilizers (PGPR) in an effort to reduce farmers' dependence on inorganic fertilizers and reduce subsidized fertilizers by the government. The research method used in this research is a factorial experiment with 2 factors with 6 treatment combinations. The first factor is biofertilizer (PGPR), R0 = without PGPR, R10 = 10 liters ha-1 PGPR and the second factor is P0 (farmers' habitual fertilization (400 kg ha-1 urea + 400 kg ha-1 NPK), P1 (100% inorganic (275 kg ha-1 urea + 250 kg ha-1 NPK)), P2 (75% inorganic (206.25 kg ha-1 urea + 187,5 kg ha-1 NPK) + 25% organic (1,25 ton ha-1)) , P3 (50% inorganic (137,5 kg h-1 Urea + 125 kg ha-1 NPK) + 50% organic (2,5 ton ha-1)), P4 (25% inorganic (68,75 kg ha-1) 1 Urea + 62,5 kg ha-1 NPK) + 75% organic (3,75 ton ha-1)), P5 (100% organic fertilizer (5 ton ha-1)). Variables observed were plant length, number of tillers, grain contents per hill, weight of 1000 seeds, productivity, leaf chlorophyll content and R/C ratio. The result shows that organic fertilizer and PGPR can be used to substitute inorganic fertilizer at 25% to 50% of the recommended dose, especially in its effect on yield. Meanwhile, substitution of 75% and 100% still not shows the effective substitution.